Improved Rhodamine B Removal Through Photocatalysis, Antibacterial Efficacy and Enhanced Room Temperature Ferromagnetism in ZnO Prepared by Chemical Bath Deposition - Suchismita Acharya; Susanta Biswal; Sachindra Sarangi (Nanochemistry Research)
The present investigation describes the preparation of ZnO and Cu-doped ZnO nanocrystals by the chemical bath deposition technique. The structure, morphology, surface chemistry, photocatalytic performance, antibacterial characteristics, and magnetic properties of both pristine and doped ZnO samples were extensively studied. The influence of copper doping on the aforementioned features were investigated systematically. Results obtained from the X-ray diffraction measurements confirmed the wurtzite hexagonal structure of ZnO, without any secondary phases. The lattice parameters of ZnO exhibited a slight variation upon copper incorporation, attributed to the substitutional replacement of Zn²⁺ by Cu²⁺ ions, which have different ionic radii. Morphological analysis of ZnO and Cu-doped ZnO nanocrystals revealed the formation of nanorod-type structures of ZnO which were modified after Cu doping. The surface chemistry and atomic bonding properties were studied by X-ray photoelectron spectroscopy, confirming the successful formation of hexagonal wurtzite ZnO. Cu-ZnO was found to be an efficient photocatalyst for the removal of Rhodamine B pollutant and achieved a degradation strength of 91.78 %. Cu-ZnO also acts as an inhibitor of bacterial growth and shows superior antibacterial features against Escherichia coli and Staphylococcus aureus. While pure ZnO exhibited ferromagnetic properties, a significant enhancement in ferromagnetic properties was observed in the Cu-ZnO sample. This enhancement is attributed to the exchange interactions between copper ions mediated by vacancies oxygen and Zn interstitials introduced by the doping process.